2019
DOI: 10.1016/j.maturitas.2019.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Older women are frailer, but less often die than men: a prospective study of older hospitalized people

Abstract: The association between frailty, mortality and sex is complex, but a limited literature is available on this topic, particularly for older hospitalized patients. Therefore, the objective of our study was to prospectively evaluate sex differences in frailty, assessed by the Multidimensional Prognostic Index (MPI) and mortality, institutionalization, and re-hospitalization in an international cohort of older people admitted to hospital. Study design: We used data from nine public hospitals in Europe and Australi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 33 publications
(38 reference statements)
6
15
0
Order By: Relevance
“…All-causes mortality was assessed by sex, and it was found that women were systematically more at risk than men under heat stress conditions. These results are in line with many studies, which identify higher mortality rates for women compared to men [4,22,57,58], specifically in the European context [21,23,25,26]. This discrepancy may arise from differences in response to thermal stress due to physiological characteristics in body temperature regulation [59,60] as well as preexisting socio-demographic characteristics in the inhabited society [11,26], such as the lower social condition that characterises elderly women, which often live alone due to longer life expectancy compared to men.…”
Section: Sexsupporting
confidence: 92%
See 3 more Smart Citations
“…All-causes mortality was assessed by sex, and it was found that women were systematically more at risk than men under heat stress conditions. These results are in line with many studies, which identify higher mortality rates for women compared to men [4,22,57,58], specifically in the European context [21,23,25,26]. This discrepancy may arise from differences in response to thermal stress due to physiological characteristics in body temperature regulation [59,60] as well as preexisting socio-demographic characteristics in the inhabited society [11,26], such as the lower social condition that characterises elderly women, which often live alone due to longer life expectancy compared to men.…”
Section: Sexsupporting
confidence: 92%
“…Therefore, the relationship between the age and the sex variable here is consistent. These results extended previous hypothesis based on the evidence that heat stress increases the susceptibility of the elderly to hot temperatures with advancing age [27,30,41,58].…”
Section: Agesupporting
confidence: 89%
See 2 more Smart Citations
“…We adjusted for these variables as neither age nor sex is included in the original MPI. Furthermore, a recent study reported a higher prevalence of women in the severe risk category [48].…”
Section: Methodsmentioning
confidence: 99%